Academic Publishing in English: Exploring Linguistic Privilege and Scholars' Trajectories. Issue 6 (2nd November 2019) - Soler, Josep
ABSTRACT: This paper explores the trajectories of six young academics (early-stage researchers) currently active in the context of Swedish academia in two different fields: English Linguistics and Political Science. Through a series of narrative interviews, the analysis investigates the development of their scholarly work, the relationship with their texts, and the negotiation of their position as contributors to their academic field. The paper discusses issues of language attitudinal and ideological nature, emphasising the need to focus on writers, rather than texts. The discussion revolves around the role of access to scholarly networks and to quality publication outlets as some of the key factors in shaping their development as young scholars and enabling opportunities to publish in highly-ranked journals. The goal of the article is to contextualise and problematize the notion of "privilege" that is customarily attributed to L1 English-speaking scholars, and to provide a more nuanced understanding of how young academics tackle the publishing enterprise.